The Effect of Blended Learning Approach on Student Satisfaction in the Learning Process at Master Degree Nursing Program in Indonesian Context - Yanny Trisyani; Etika Emaliyawati; Ayu Prawesti Priambodo; Ristina Mirwanti; Donny Nurhamsyah (Padjadjaran Acute Care Nursing Journal, 2019)
Nursing education at post graduate degree aims to produce graduates with the essential competencies as researchers which are closely related to the capability of implementing information technology which are in the global health era. However, the implementation of blended learning which combines e-learning approach into the learning process has characterised with various challenges for students and lecturers. These study aims are to identify the effect of the blended learning approach to student satisfaction on the learning process in the master's degree nursing program in Indonesian context.Method: The study was conducted in 2018, the quantitative approach has been utilized. Participants in this study are 88 post graduate nursing students who were selected with purposive sampling. Data collection was conducted through survey and analysis correlational with Pearson test.Finding of the study has indicated that the Blended learning approach as indicated in: Quality of Learning Process (QLP) in terms of Student Engagement and Accessibility & interactivity on average is 83% favourable and 17% unfavourable; and QLP from students’ perspective is 58, 96% favourable and 41.04 % unfavourable. Student satisfaction with blended learning process on average is 54.75% favourable and 45.25% unfavourable. The results of the Pearson analysis have shown that there is a very weak correlation between the Blended Learning approach and Student Satisfaction with correlation value of 0.180 and Significance value of 0.864. In this case, almost all participants stated that blended learning is essential as it makes the learning process more innovative and it motivates independent learning.